THE EFFECTIVENESS OF MULTIPLE INOCULATION OF BIODIVERSITY IN IMPROVING SOIL BIOLOGICAL PROPERTIES AND RESULTS OF TWO GOGO RICE VARIETIES IN COASTAL AREA - Aisah Putri Anggraini; Yudhi Harini Bertham; Abimanyu Dipo Nusantara (Asosiasi Mikoriza Indonesia, 2022)
This study aims to obtain a combination of biological fertilizers and upland rice varieties that can improve soil biological properties and increase upland rice production in coastal areas. This research was conducted from September to December 2019, in Beringin Raya Village, Muara Bangkahulu District, Bengkulu City. Soil and plant analysis were carried out at the Soil Science Laboratory, Faculty of Agriculture, Bengkulu University. This study used a Completely Randomized Block Design (RAKL). The first factor tested was upland rice varieties consisting of Inpago 10 and Serantan. Furthermore, the second factor is the type of biological fertilizer which consists of control, a combination of P solubilizing bacteria, K solubilizing bacteria, and N2 fixing bacteria, as well as a combination of arbuscular mycorrhizal fungi, K solubilizing bacteria, and N2 fixing bacteria. Each treatment combination was repeated 4 times so that there were 24 experimental units. Each experiment consisted of 50 plants so that the total plant population was 50 x 24 = 1,200 plants. The results showed that the combination of double inoculants of biological fertilizers BPF + BPK + BPN and rice variety Inpago 10 resulted in the highest population of potassium solubilizing bacteria, plant dry weight and weight of pithy grain per clump. Double inoculants of BPF + BPK + BPN biofertilizers resulted in the highest population of potassium solubilizing bacteria, the heaviest plant dry weight and weight of pithy grain per clump. Inpago 10 variety also had a higher population of potassium solubilizing bacteria, and better growth and yield components of rice compared to the serantan variety.